Manajemen Pengelolaan Sumber Daya Insani (SDI) di Lembaga Zakat Infaq dan Shadaqah Muhammadiyah (LAZISMU) Ponorogo - Rois, Adib Khusnul; Zahara, Jihan Nabila; Irsyaadullah, Ahnaf Nabil (Universitas Muhammadiyah Ponorogo, 2025)
This study discusses Human Resources in LAZISMU Ponorogo with professional system management. The background of this study is that Human Resources are the most important part of an institution and organization, Human Resources are a crucial aspect in the success of managing zakat, infak, shodaqoh and waqf (ZISWAF) by the LAZISMU Ponorogo zakat institution. The research method in this study is qualitative descriptive analysis. By explaining the phenomena that occur in the zakat institution (LAZ). Data were collected through interviews, observations, and documentation from directors and employees at LAZISMU Ponorogo. The results of the study indicate that Human Resources in LAZISMU Ponorogo can have good abilities, professional in work that has Knowledge and Skills, Communication and Interpersonal Skills, Character Excellence, Human Resource Development, Management and Leadership. The programs implemented in LAZISMU Ponorogo to improve SDI are as follows: 1. Providing Education on SDI, 2. Economic Empowerment in LAZISMU Ponorogo, 3. Social Empowerment in LAZISMU Ponorogo, 4. Community Empowerment in LAZISMU Ponorogo, 5. Improving Digital Skills in LAZISMU Ponorogo.